Designing Effective Mathematics Learning : Augmented Reality Framework Development via the Fuzzy Delphi Method - Nur Izza Nabila, Ahmad; Syahrul Nizam, Junaini; Suriati Khartini, Jali (2023)
In the current era where Augmented Reality (AR) is making significant impact on various aspects of education, its specific role in mathematics education is of crucial significance. A quantitative research design was employed, utilizing the Fuzzy Delphi technique to collate opinions from a diverse group of 17 experts drawn from fields such as education, User Interface / User Experience (UI/UX), mobile app development, AR/VR, mathematics, computer science, and educational technology. The data analysis indicated a consensus among the experts on the key elements necessary for creating effective AR applications in mathematics education, as evidenced by values exceeding 75% agreement, with a maximum acceptable dispersion of opinions (d) ≤ 0.2, and a minimum consensus measure (fuzzy score, ≥ α-cut value larger than 0.5). The findings underscore the importance of the identified components in the design and development of AR applications for mathematics education and signal significant potential for promoting technology-enhanced active learning in the educational field.